P2X7 Receptor Stimulation Is Not Required for Oxalate Crystal-nduced Kidney Injury - Luz, Hannah L.; Reichel, Martin; Unwin, Robert J.; Mutig, Kerim; Najenson, Ana C.; Tonner, Louise M.; Eckardt, Kai-Uwe; Tam, Frederick W. K.; Knauf, Felix (Scientific Reports, 2019)
Oxalate crystal-induced renal inflammation is associated with progressive kidney failure due to activation of the NLRP3/CASP-1 inflammasome. It has been suggested previously that purinergic P2X7 receptor signaling is critical for crystal-induced inflammasome activation and renal injury. Therefore, we investigated the role of the P2X7 receptor in response to crystal-induced cytokine release, inflammation, and kidney failure using in vitro and in vivo models. Dendritic cells and macrophages derived from murine bone marrow and human peripheral blood mononucleated cells stimulated with calcium-oxalate crystals, monosodium urate crystals, or ATP lead to the robust release of interleukin-1beta (IL-1 beta). Treatment with the P2X7 inhibitor A740003 or the depletion of ATP by apyrase selectively abrogated ATP-induced, but not oxalate and urate crystal-induced IL-1 beta release. In line with this finding, dendritic cells derived from bone marrow (BMDCs) from P2X7(-/-) mice released reduced amounts of IL-1 beta following stimulation with ATP, while oxalate and urate crystal-induced IL-1 beta release was unaffected. In sharp contrast, BMDCs from Casp1(-/-) mice exhibited reduced IL-1 beta release following either of the three stimulants. In addition, P2X7(-/-) mice demonstrated similar degrees of crystal deposition, tubular damage and inflammation when compared with WT mice. In line with these findings, increases in plasma creatinine were no different between WT and P2X7(-/-) mice. In contrast to previous reports, our results indicate that P2X7 receptor is not required for crystal-induced CKD and it is unlikely to be a suitable therapeutic target for crystal-induced progressive kidney disease.
CRIS-Team WoS Importer:2020-02-07